30 July 2018 Fluorescence imaging for crop stress monitoring - Yadav, Brijesh; Yadav, Poonam (Indian Farming, 2018)
Chlorophyll fluorescence analysis is widely used to evaluate the photosystem II (PSII) activity, which is an important target of biotic and abiotic stresses. By using these techniques for crop monitoring would allow us to alleviate stress at an early stage and thus substantially reducing yield losses.